As conferências cívicas e o livro de leitura Terra Gaúcha : as aspirações nacionalistas de João Simões Lopes Neto (1865-1916) - Porto, Aline Carvalho (2015)
This dissertation will analyze the Conferências Cívicas (1904-1906) and the spelling book Terra Gaúcha (2013), both by João Simões Lopes Neto. On this basis, we intend to comprehend how the author has organized and expressed his ideas concerning the Brazilian nation, what were his inspirations and the lines of thought that most influenced him. With this in mind, this research aims to increase the understanding about Lopes Neto and his work. In other words, the objective is to understand him not only as a regionalist writer but as an intellectual who, from your region, thought about the Brazilian nation. This expansion of perspective about Lopes Neto contributes to a better understanding of the author and his work. When thinking about the Brazilian nation, Lopes Neto realized the lack of a civic education able to awaken in people "the spirit of the nation". Trying to solve this problem the author created a complex narrative in order to pay attention to the virtues and vices of the Brazilian nation, its different regions and cultures. For example, the spelling book would be a tool for teaching in Rio Grande do Sul. So it has special focus on the gaucho culture and tries to demonstrate that the various regions form the nation.